What has changed? Care home work during the pandemic in Jack Thornes’ Help: No one is coming - Goulding, Anna (Age, Culture, Humanities: An Interdisciplinary Journal, 2023)
The article examines how Jack Thornes’ Help: No one is coming (2021) politicizes the public sphere of dementia care. The drama’s focus on care homes in the UK during the pandemic addresses the impact of the crisis and simultaneously serves to highlight the longstanding issues faced by an under-funded and under-valued sector. This paper aims to examine how Help reflects, but also writes societal scripts about how we care for our populations with dementia and the people we pay to care for them. In highlighting the pressure care homes are under, it is important to look at our collective societal attitude to care, and whether we are prepared to cover higher wages that would be required if care work became a desirable career with progression. In examining the purpose of, and effectiveness of the drama’s rhetoric, I aim to investigate how ideological notions of care and practical care work are articulated. Finally, I ask whether Help succeeds in mobilizing audiences to press for change or whether in its portrayal of care homes, the drama enables them to accept the status quo. Submitted: 16 November 2022 Acctepted: 7 August 2023 Published 12 September 2023